Tweet, Post, Share: Decoding Personality and Gender Effects on Social Media Self-Disclosure among University Undergraduates - Oluwafemi P Famakinde; Hammed A Arowosaye; Emmanuel E Uye (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
Social media is an emerging social platform through which millions of people share information and interact with one another daily. Studies on the predictors of self-disclosure on social media tend to give varying results. Therefore, this study investigated personality traits and gender as predictors of self-disclosure on social media among university undergraduates. The study adopted a cross-sectional survey design while a purposive sampling technique was used to select the study population. Data were collected from 301 undergraduates using validated questionnaires and analyzed using an independent samples t-test and multiple regression analysis at p < 0.05 level of significance. The result showed that personality traits of extraversion, agreeableness, openness to experience, conscientiousness and neuroticism jointly predicted self-disclosure on social media among study participants. Also, the result revealed that gender significantly influences self-disclosure on social media among study participants such that female undergraduates were higher in self-disclosure on social media than their male counterparts. The study concluded that personality traits and gender are strong predictors of self-disclosure on social media among study participants.